La publicidad y promoción y su incidencia en el posicionamiento de la empresa “Jara acabados de construcción” en la ciudad de Riobamba - Carlos Alfredo, Guerrero Andrade (2021)
ABSTRACT The current situation of commercial companies has become critical. Only the application of innovative and emerging sales strategies will make it possible for them to survive. In this context, it is proposed to carry out this research to establish the incidence of advertising and promotion in the positioning of the company Jara Finishes of construction. For this, an analysis of the company's current situation was carried out, based on previous theoretical analysis, and applying a survey applied to customers and interviews with employees and strategic partners of the company. The results obtained indicate that the company has positioned itself adequately in the market using strategic means to maintain accessible prices of the products and adequate service. However, this has ceased to be efficient in the market, noting a progressive stagnation that has become even more complicated with the health emergency, so we propose an advertising and promotion plan that according to the needs of the company and considering current trends is oriented to digital media, the internet, and the use of social networks. This strategic plan consists of nine advertising strategies aimed at giving efficiency to digital marketing processes considering the characteristics of current and potential customers linked to social networks and the structure of a promotional system that improves sales and increases the sales level of clients and strategic partners. Keywords: Advertising, promotion, positioning, digital marketing, social networks Translation Reviewed by: Mgs. Elizabeth Diaz ENGLISH PROFESSOR c.c. 0603277765